2017
DOI: 10.3389/fphys.2017.00394
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of SIRT6 in a Mouse Model of Transverse Aortic Constriction-Induced Heart Failure

Abstract: SIRT6, a member of the NAD (+)-dependent class III deacetylase sirtuin family, plays important roles in the maintenance of cardiovascular homeostasis. Telomere shortening is a risk factor for age-associated diseases, including heart disease. In the present study, we investigated the role of SIRT6 and telomerase in a mouse model of transverse aortic constriction (TAC)-induced heart failure. SIRT6, telomerase reverse transcriptase (TERT), and telomere repeat binding factor (TRF)-1 were significantly downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…24 As an important member of sirtuin family, SIRT6 is mainly located in the nucleus and its activation exerts protective effects against myocardial infarction, 25 cardiac hypertrophy, 26 and heart failure. 27 Besides, numerous studies have reported that sirtuins mediated the pleiotropic actions of melatonin in various disease models. 24 However, to the best of our knowledge, there are few studies investigating the role of SIRT6 in the modulatory actions of melatonin in pathological condition.…”
Section: Introductionmentioning
confidence: 99%
“…24 As an important member of sirtuin family, SIRT6 is mainly located in the nucleus and its activation exerts protective effects against myocardial infarction, 25 cardiac hypertrophy, 26 and heart failure. 27 Besides, numerous studies have reported that sirtuins mediated the pleiotropic actions of melatonin in various disease models. 24 However, to the best of our knowledge, there are few studies investigating the role of SIRT6 in the modulatory actions of melatonin in pathological condition.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that SIRT6 knockdown in oocytes causes the reduction in telomere length in early embryos. Telomere-binding proteins TRF1 and TRF2 bind specifically to the double-stranded TTAGGG repeats, and are important for the control of telomeric length and structure [33]. TRF1 has been reported to play a key role in both telomerase-dependent telomere maintenance and alternative lengthening [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…damage, Gao et al (41) observed that SIRT6 was required for directional telomere movement, a process that facilitates efficient DNA damage repair at telomeric chromatin. Additionally, SIRT6 overexpression in mice was reported to up-regulate telomerase reverse transcriptase and telomere repeat binding factor, although this study did not explore the mechanism of upregulation or potential downstream effects on telomere length (42). Proper mitosis requires condensed and silenced pericentric heterochromatin at centromeres to protect against genomic instability and cellular senescence during cell division.…”
Section: Dna Repair and Chromatin Maintenancementioning
confidence: 95%